Prinsip-Prinsip Yang Terkandung Dalam Batang Tubuh UUD 1945 - Kartini; Khairul Fikri; Nadine Khalifi Ermawan; Fahman Al Hanafi Kudadiri; Muhammad Rifai Alhabib (CV. SINAR HOWUHOWU, 2025)
The 1945 Constitution of the Republic of Indonesia (UUD 1945) is the highest legal foundation that regulates the structure of government, the rights and obligations of citizens, and the direction of the implementation of national and state life. The body of the 1945 Constitution contains basic principles that reflect the values of Pancasila and the spirit of independence, democracy, and social justice. This article examines in depth the principles contained in the body of the 1945 Constitution, including equality before the law, freedom of religion, human rights, the national cultural system, and national defense. This study uses a literature study method with a normative approach. The results of the study show that the body of the 1945 Constitution is flexible and able to adapt to developments in the era, and is a foundation for realizing a democratic system of government, guaranteeing the constitutional rights of citizens, and strengthening national unity within the framework of the Unitary State of the Republic of Indonesia.